Plastic deformation behavior of ultrafine grained CoCrFeNiMn high entropy alloy with nanoparticles. (March 2022) - Xie, Yuehuang; Zhang, Zhen; Luo, Yifei; Wang, Jun; Liang, Jiamiao; Zhang, Deliang
Abstract: High strength ultrafine grained CoCrFeNiMn high entropy alloys (HEAs) containing TiO(C) nanoparticles were fabricated by thermomechanical consolidation of a mechanically milled powder at 950 and 1000 °C, respectively. The sample consolidated at 950 °C with an average grain size of 417 nm had a high yield strength (YS) of 1457 MPa, but exhibited necking immediately after yield drop, leading to a limited elongation to fracture of 1.3%. In contrast, the sample consolidated at 1000 °C with an average grain size of 489 nm had a clearly lower YS of 1236 MPa, but exhibited yield drop, Lüders deformation, work hardening and then necking, with a significant elongation to fracture of 10.0%. Our work shows that by introducing intragranular Ni–Ti nanoparticles in the coarser grained sample through quenching to liquid nitrogen and aging, the YS of the sample was brought back to 1449 MPa, and still kept a substantial elongation to fracture of 4.2%. The transition of the plastic deformation behavior with grain refinement is analyzed based on dislocation dynamics theory. Based on this analysis, it is proposed that to maintain the uniform deformation, the grain sizes should be larger than a critical value, above which maximum flow stress of the material is higher than the upper yield stress. Introducing intragranular Ni–Ti nanoparticles is an effective strategy to further enhance yield strength without losing work hardening ability due to the synergistic effect with intragranular TiO(C) nanoparticles to inhibiting dislocation annihilation at grain boundaries. Highlights: Remarkable transition of plastic deformation behavior occurs with grain refinement. Intragranular nanoparticles pin dislocations and inhibit dislocation annihilation. Cracks initiate around intergranular nanoparticles due to stress concentration.